Intensitas Dukungan Keluarga Dalam Mengurangi Tingkat Stres Pada Warga Binaan Wanita Di Lembaga Pemasyarakatan - Sati, Ali; Harahap, Sari (Institut Agama Islam Negeri Padangsidimpuan, 2020)
This research is motivated by fostered residents who have difficulty adjusting their lives in the penitentiary. Other than that, they have to part with their families, loss of goods and services owned, lost the freedom to live outside. Therefore, the existence of family support so that fostered residents avoid stressful conditions because women fostered citizens need motivation, comfort and calmness. The type of this research is field research, which aims to obtain information and describe events in accordance with the facts in the field, This research uses a qualitative approach with descriptive analysis. The results of the research are the intensity of family support in visiting women-assisted citizens in Penitentiary Class II B Padangsidimpuan able to reduce the stress level of women-assisted citizens because it can be seen that the conditions of women-assisted women who are very frequent and frequently visit their families within a month experience moderate stress levels, As for women-assisted residents who are in the category sometimes and have not been visited by their families in a month experiencing severe stress levels. Stressful conditions include psychological and physiological conditions for women assisted by Class II B Penitentiary, experiencing unfavorable or unhealthy conditions because women who are fostered by women are still very often anxious, difficult to sleep, like to be alone, moody, easily offended, irritable, even irritable diseases such as headaches and lack of enthusiasm in carrying out daily activities in prison.